Ionic Colloidal Molding as a Biomimetic Scaffolding Strategy for Uniform Bone Tissue Regeneration. Issue 17 (21st February 2017) - Zhang, Jian; Jia, Jinpeng; Kim, Jimin P.; Shen, Hong; Yang, Fei; Zhang, Qiang; Xu, Meng; Bi, Wenzhi; Wang, Xing; Yang, Jian; Wu, Decheng
Abstract : Inspired by the highly ordered nanostructure of bone, nanodopant composite biomaterials are gaining special attention for their ability to guide bone tissue regeneration through structural and biological cues. However, bone malformation in orthopedic surgery is a lingering issue, partly due to the high surface energy of traditional nanoparticles contributing to aggregation and inhomogeneity. Recently, carboxyl‐functionalized synthetic polymers have been shown to mimic the carboxyl‐rich surface motifs of non‐collagenous proteins in stabilizing hydroxyapatite and directing intrafibrillar mineralization in‐vitro. Based on this biomimetic approach, it is herein demonstrated that carboxyl functionalization of poly(lactic‐co‐glycolic acid) can achieve great material homogeneity in nanocomposites. This ionic colloidal molding method stabilizes hydroxyapatite precursors to confer even nanodopant packing, improving therapeutic outcomes in bone repair by remarkably improving mechanical properties of nanocomposites and optimizing controlled drug release, resulting in better cell in‐growth and osteogenic differentiation. Lastly, better controlled biomaterial degradation significantly improved osteointegration, translating to highly regular bone formation with minimal fibrous tissue and increased bone density in rabbit radial defect models. Ionic colloidal molding is a simple yet effective approach of achieving materials homogeneity and modulating crystal nucleation, serving as an excellent biomimetic scaffolding strategy to rebuild natural bone integrity. Abstract : A novel scaffolding strategy utilizing an ionically colloidal molding method to stabilize nanoparticles during fabrication is developed to construct highly uniform nanocomposite scaffolds that greatly improve therapeutic outcomes compared to traditionally mixed nanocomposites, and even more remarkably, elicit significantly less fibrous tissue encapsulation and prevent symptoms of bone malformation such as multiple chambers and irregular medullary cavities.